A Porous Zn2(abct) Framework as an Efficient Carrier for 5‐Fu Delivery and Inhibiting Human Liver Cancer Cells. Issue 10 (6th May 2018) - Song, Bao‐Hua; Ding, Xing; Li, Chen; An, Gui‐Feng
Abstract : The creation of effective drug delivery systems is very important in diagnosis and treatment of cancer through controlled and targeted drug delivery. They can increase bioavailability of drugs and reduce their side effects. Metal‐organic frameworks (MOFs) are alternative drug delivery systems, which are suitable for targeted drug delivery due to their adjustable pore sizes and compatibility by adding some functional groups. In this work, a new porous Zn II ‐organic framework was fabricated using a tetracarboxylic acid linker 3, 3′, 5, 5′‐azobenzene‐tetracarboxylic acid (H4 abct), which reveals a 3D channel‐type framework with a high free pore volume. The performance of the solvent‐free samples was studied on absorbing and releasing 5‐fluorouracil (5‐Fu). Characterization methods, such as FT‐IR, PXRD, HPLC, BET measurement, and GCMC simulations, were employed to characterize the 5‐Fu loaded framework. Furthermore, anticancer properties of the MOF and drug‐loaded MOF were investigated against four human liver cancer cells (HepG2, SMMC‐7721, HuH‐7 and MHCC‐97H). Abstract :